A case study: the benefits and challenges of root cause analysis presented through a real world example from the rail industry. Issue 4 (2nd October 2017) - Denniss, Steve
Abstract: This paper presents the key elements relating to a powerful tool, root cause analysis (RCA), and then explores the practicalities of applying this tool to a real life example on the railway. RCA can be a useful technique in getting to the source of a problem. However, to get the most from RCA one must recognise that the resulting recommendations may be difficult to implement due to practicalities and cost constraints. Being able to determine the most beneficial and affordable remedial action to take is a key outcome of the process. Therefore, RCA must be carried out with consideration of how big the problem is, and whether curing the cause is worse than coping with the effect. Experience gained from the example used in this paper, which is from the rail industry, illustrates how complex the underlying decision making process may be and how the output from the RCA can help to inform this process.